Kinematic determinants and physiological response of cross-country skiing at maximal speed - Stöggl, T. L.; Müller, E. (Medicine & Science in Sports & Exercise, 2009)
Purpose: The scope of the study was to a) transfer the maximal anaerobic running test (MART) to a treadmill-based cross-country roller skiing test protocol for skating and classic style, b) analyze the development and determinants of kinematic and physiological parameters from submaximal to maximal skiing speeds, c) analyze the effects of fatigue on skiing technique, and d) test the hypotheses that maximal skiing speed is related to cycle length and that the fastest skiers show shorter thrust combined with longer swing phases.